The Effectiveness Of Umbilical Cord Care With Topical Breast Milk On The Length Of Umbilical Cord Detachment In Newborns At The Yusniar Clinic Pangkalan Berandan In 2022 - Rahmaini Fitri Harahap; Defi Sentiyani Ramadani; Anizar; Cut Yusnidar; Debora Dea Zerlina Jesse (Institute of Computer Science (IOCS), 2022)
Umbilical cord that is not cared for properly can cause infection of the umbilical cord. The umbilical cord usually sheds 1 week after birth and the wound heals within 15 days. Wounds that have not healed are a pathway for germs to enter which result in infection, which can quickly lead to sepsis. The purpose of this study was to determine the effectiveness of topical breast milk treatment of the umbilical cord on the length of time for the release of the umbilical cord in newborns. This type of research uses a quasy experimental research design with a control group design. This research was conducted at the Yusniar Pangkalan Berandan Clinic. This research was conducted in August 2022. The population in this study were all newborns born at the Yusniar Clinic. The sample in this study were all newborns born in August - September 2022. The subject-taking technique used a total sampling of 40 people. Subjects were divided into two groups, an intervention group and a control group, each of which consisted of 20 people. The intervention group was given treatment with umbilical cord care using topical breast milk while the control group was treated with dry gauze. Then measurements are taken when the umbilical cord is released, quickly if it is released within 1-7 days and normal if it is released within 8-14 days. The type of data used in this study is primary data. Data collection is assisted by enumerators. Data analysis with the Wilcoxon rank test. The results of the study were obtained based on the duration of the release of the umbilical cord with topical ASI, the majority of normal umbilical cord discharge were 16 people (80%), and the minority of slow cord discharge was 1 respondent (5%). Based on the duration of the release of the umbilical cord with dry gauze, the majority of the release of the umbilical cord were slow, as many as 16 people (80%), and the minority of normal umbilical cord discharge were 4 respondents (20%). Based on the Mann Whitney test, the results obtained were a p value of 0.000. Treatment of the umbilical cord with topical breast milk was effective for the duration of the release of the umbilical cord in newborns. Umbilical cord care with topical breast milk is effective for the duration of umbilical cord discharge in newborns.